Efektivitas Pembelajaran Daring Di Masa Pandemi Covid-19 - Inne Nuriel Primestike; Qatrunnada Salsabila (Sadida Islamic Communications and Media Studies, 2021)
The purpose of this study was to identify obtaining information about the obstacles to the online teaching and learning process at home as a result of the COVID-19 pandemic. This research is entitled "effectiveness of online learning during the covid19 pandemic" to find out how student innovations increase the effectiveness of online learning and create conducive learning, this research is a research that uses a descriptive method with a qualitative approach, data collection techniques and uses interviews with informants who come from from the student side, namely the university of uin ar - raniry, the determination of the informants using random sampling technique, in this study the respondents were 15 students at the uin ar - raniry university, the interview method used the semi-structured interview method, a list of questions prepared for the interview was developed based on the related literature, the results of this study there are students who still have obstacles in online learning activities, namely, lack of mastery of technology, additional internet quota fees, additional work to help parents, lack of socialization between students.